2017
DOI: 10.29011/2577-1493.100023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feeding Rate and Diet Oil Source on Growth Performance and Feed Utilization of Rabbitfish (Siganus rivulatus) Fry

Abstract: This study was conducted to determine the optimum feeding rate and evaluate the total replacement of fish oil as main source of fat by linseed oil from diet on growth performance and feed utilization of rabbitfish fry. This trial was factorial (3x2) and continued for 114 days. The average initial weight (W1) of fry was 0.18±0.012 g and the average initial length (L2) was 2.76 cm±0.05. This trial tested two factors, the feeding rate (5%, 7% and 9% of fish body weight) with two diets (36.44% CP) differed in oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
2
0
0
Order By: Relevance
“…However, fat level decreased significantly with increasing feeding levels. Similar results were recorded by Mohammed et al ( 2017 ); they illustrated that the whole fish body content of protein did not affected with increasing feeding levels. Generally, in the present study, using 15% grape pomace in the fish diet significantly increased growth performance, survival, HSI, and VSI indices.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…However, fat level decreased significantly with increasing feeding levels. Similar results were recorded by Mohammed et al ( 2017 ); they illustrated that the whole fish body content of protein did not affected with increasing feeding levels. Generally, in the present study, using 15% grape pomace in the fish diet significantly increased growth performance, survival, HSI, and VSI indices.…”
Section: Resultssupporting
confidence: 90%
“…Morphological statistical analysis in the present study showed that increased significantly with increasing feeding rate. This observation was in agreement with the report of Mohammed et al (2017) who found that HSI did not differ among the treatments by the change of feeding level; in the same trend, Du et al (2006) ascertain that HSI did not affect with increasing feeding rate.…”
Section: Body Compositionsupporting
confidence: 93%